Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis

The art of feminism: images that shaped the fight for equality, 1857-2017 - Arakistain, Xabier; Balshaw, Maria; Gosling, Lucinda; Reckitt, Helena; Robinson, Hilary; Tobin, Amy; Reckitt, Helena; Gosling, Lucinda; Robinson, Hilary; Tobin, Amy; Balshaw, Maria; Arakistain, Xabier (Chronicle Books, 2018)
Featured artists include: Beyonce, Louise Bourgeois, Andrea Bowers, Judy Chicago, Vanessa German, Jenny Holzer, Frida Kahlo, Barbara Kruger, AnaMendieta, Sethembile Msezane, Zanele Muholi, Shirin Neshat, Pussy Riot.Since its inception, the women's movement has harnessed the power of the image to transmit its message. From the posters of the Suffrage Atelier, to the photographs of Carrie Mae Weems, this comprehensive survey traces the ways in which feminists have shaped art and visual culture from the mid-nineteenth to the twenty-first centuries. Featuring more than 350 works of art, illustration, photography, performance, graphic design, and publlic protest, this stunning volume showcases the vibrancy and daring of the feministaesthetic over the last 150 years.
Keywords: 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; arts; cours; discipline; discours; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Desire change: contemporary feminist art in Canada - Davis, Heather M. (Heather Margaret); Mentoring Artists for Women's Art (McGill-Queen's University Press ;, 2017)
"In the resistance to the violence of gender-based oppression, vibrant - but often ignored - worlds have emerged, full of nuance, humour, and beauty. Correcting a glaring omission of writing about contemporary feminist work by Canadian artists, Desire Change considers the resurgence of feminist art, thought, and practice in the past decade by examining artworks that respond to themes of diversity and desire. Essays by historians, artists, and curators present an overview of a range of artistic practices including performance, installation, video, textiles, and photography. Contributors address the desire for change through three central frames: how feminist art has significantly contributed to the complex understanding of gender as it intersects with sexuality and race; the necessary critique of patriarchy and institutions as they relate to colonization within the Canadian national-state; and the ways in which contemporary critiques are formed and expressed. The resulting collection addresses art through an activist lens to examine intersectional feminism, decolonization, and feminist institution building in a Canadian context. Heavily illustrated with representative works, Desire Change raises both the stakes and the concerns of contemporary feminist art, with an understanding that feminism is always and necessarily plural."-- Provided by publisher.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; arts; canada; cours; discipline; femmes* artistes; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; patriarcat; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques

Stitching through Silence: Walking With Our Sisters, Honoring the Missing and Murdered Aboriginal Women in Canada - Anderson, Stephanie G. (TEXTILE, 2016)
This article explores the complex relationship between processes of making, memory, healing, and social activism activated by Walking With Our Sisters, a large-scale commemorative installation intended to foster awareness for missing and murdered Indigenous women in Canada.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; art autochtone; art contemporain; artistes autochtones; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; féminicide; féminisme autochtone; histoire de l'art; histoire et politique; militance; perlage; pol4105; premier cycle; périodes historiques; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Feminist avant-garde: art of the 1970s : the Sammlung Verbund Collection, Vienna - Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); Palais des beaux-arts (Bruxelles, Belgique); Mjellby konstmuseum; Hamburger Kunsthalle; Photographers' Gallery; Museum Moderner Kunst (Autriche); Sammlung Verbund.; Schor, Gabriele; Galleria nazionale d'arte moderna (Italie); Círculo de Bellas Artes (Madrid, Espagne); et al. (Prestel, 2016)
Featuring a wide variety of work from artists both well-known and under the radar, this dynamic book reveals how women artists reclaimed control of the feminine image in photography, video, and performance art. This book documents a tectonic change in the way women portray themselves in art. Historically, women were depicted as a projection of male fantasies, prejudices, and relationships. However in the 1970s, for the first time, female artists began collectively to investigate visual representations of their own selves. They studied their own bodies and created the prospect of determined feminine identities. Editor Gabriele Schor explores the Feminist Avant-Garde to emphasize the role that these artists played for the last four decades. The works are provocative, radical, poetic, ironic, angry, cynical and heartfelt. The artists shared a collective consciousness that reassessed, and even rejected, what came before, turning to new ways of expression in the fields of photography, performance, film, and video. The collection SAMMLUNG VERBUND founded in 2004 in Vienna focuses on the feminist art movement of the 1970s as one of the main areas and is with 500 works the largest collection with this emphasis. Included are works by Eleanor Antin, Cindy Sherman, Ana Mendieta, Nil Yalter, Ketty La Rocca, Birgit Jürgenssen, Renate Bertlmann, Francesca Woodman and others. This important book emphasizes the accomplishments of women artists who have made a name for themselves while encouraging the young generation.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; biographie; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; patriarcat; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Comment être artiste, femme et autochtone au Canada ? Du stigmate à son renversement dans l'art contemporain - Goyon, Marie (Sociologie de l'Art, 2011)
Résumé Cet article analyse les usages de savoir-faire genrés dans la création contemporaine autochtone canadienne. Ils sont considérés dans leur caractère doublement situé, culturel et sexué. Comment analyser les usages des savoir-faire dits « féminins » (couture, broderie) dans les œuvres de plasticiennes contemporaines ? La réflexion s’appuie sur l’étude des trajectoires biographiques et des œuvres de trois artistes canadiennes autochtones. Une double stigmatisation de ces artistes, marquée de stéréotypes ethniques et genrés, est repérée dans les conditions d’exposition de leurs œuvres en tant qu’autochtones (musées d’ethnologie) et en tant que femmes (musées locaux, statut non professionnel des créatrices). Leurs démarches pourront être qualifiées de postcoloniales, interrogeant les frontières normatives entre arts « majeurs » et arts « mineurs », ainsi que la place des arts « premiers » et des femmes créatrices dans l’histoire de l’art
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amériques; approches et analyses; art contemporain; art textile; artisanat; artistes autochtones; arts; arts textiles; canada; cours; discipline; femmes* artistes; féminisme autochtone; féminisme décolonial; har4600; histoire de l'art; histoire et politique; intersectionnalité; pol4105; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; travaux d'aiguilles

« Your Body is a Battleground » De quelques objets de l'histoire de l'art - Mader, Rachel; Schweizer, Nicole (Nouvelles Questions Féministes, 2005)
Notre article s'articule autour des points suivants: comment la critique féministe de histoire de l'art a-t-elle déplacé le ou les «objets» autour desquels s'articulait traditionnellement la discipline? Quels nouveaux «objets» ont dès lors été constitués? Et comment, à l'épreuve de ceux-ci, les histoires de l'art féministes doivent-elles, elles aussi, constamment se repositionner? L'exemple paradigmatique du corps dans la performance des années 70 nous permet d'interroger dans un deuxième temps la façon dont les artistes elles-mêmes ont déplacé la définition de l'objet, et par conséquent aussi celle du sujet - de l'œuvre comme de la perception.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; artistes féministes; arts; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; patriarcat; performance; premier cycle; périodes historiques; représentation des femme*; ressource en ligne; sex2283; sexisme; systèmes d'oppressions; thématiques

Women making art: history, subjectivity, aesthetics - Meskimmon, Marsha.. (Routledge, 2003)
Women have been making art for centuries, yet their work has been seen as secondary or has gone unrecognized altogether. "Women making art" asks why this is so, and what it would take for us to realize the extent of women's extraordinary contribution to the arts. Marsha Meskimmon mobilizes contemporary feminist thinking to reconsider how and why women have made art. She examines work by a wide range of women artists fomr different cultures and historical periods, including Rebecca Horn, Rachel Whiteread, Shirin Neshat and Maya Lin, emphasizing the diversity of women's arts and the importance of differences between women.
Keywords: 1900-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; art contemporain; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Women in Dada: essays on sex, gender, and identity - Sawelson-Gorse, Naomi (The MIT Press, 2001)
Finally, a look at the role of women in the shaping of the high-spirited—but hardly feminist—Dada monement. For all of its iconoclasm, the Dada spirit was not without repression, and the Dada movement was not without misogynist tendencies. Indeed, the word Dada evokes the idea of the male—both as father and as domineering authority. Thus female colleagues were to be seen not heard, nurturers not usurpers, pleasant not disruptive.This book is the first to make the case that women's changing role in European and American society was critical to Dada. Debates about birth control and suffrage, a declining male population and expanding female workforce, the emergence of the New Woman, and Freudianism were among the forces that contributed to the Dadaist enterprise. Among the female dadaists discussed are the German émigré Baroness Elsa von Freytag-Loringhoven; Berlin dadaist Hannah Höch; French dadaists Juliette Roche and Suzanne Duchamp; Zurich dadaists Sophie Taeuber and Emmy Hennings; expatriate poet and artist Mina Loy; the "Queen of Greenwich Village," Clara Tice; Margaret Anderson and Jane Heap, the lesbian couple who ran The Little Review; and Beatrice Wood, who died in 1998 at the age of 105. The book also addresses issues of colonialist racism, cross-dressing and dandyism, and the gendering of the machine. The bibliography was compiled by the International Dada Archive (Timothy Shipe and Rudolf E. Kuenzli). Contributors Eleanor S. Apter, Barbara J. Bloemink, Willard Bohn, Carolyn Burke, William A. Camfield, Whitney Chadwick, Dorothea Dietrich, Susan Fillin-Yeh, Paul B. Franklin, Renée Riese Hubert, Marisa Januzzi, Amelia Jones, Marie T. Keller, Rudolf E. Kuenzli, Maud Lavin, Margaret A. Morgan, Dickran Tashjian, Elizabeth Hutton Turner, Barbara Zabel
Keywords: 1900-1999; 1910-1919; allemagne; amériques; approches et analyses; arts; cours; discipline; europe; femmes* artistes; france; har4600; histoire de l'art; histoire et politique; inégalités; premier cycle; périodes historiques; régions géographiques; sexisme; suisse; systèmes d'oppressions; thématiques; états-unis